Curbing Students' Bullying Among Secondary School Learners: The Effectiveness of School Bullying Interventions - Kioko, Joseph Wambua; Njihia, Mukirae; Mutune, Susan (Journal Integration of Social Studies and Business Development, 2024)
This study investigates the effectiveness of bullying interventions in addressing student bullying within secondary schools in Machakos County. Anchored on social learning theory, which elucidates the role of behavior in fostering bullying among learners, the research employed a descriptive survey research design to gather and analyze primary data. A sample of 333 respondents was drawn from a population of 116,053 individuals across 36 schools. Questionnaires and interview guides served as the primary research instruments. The analysis encompassed both qualitative and quantitative methods. Results revealed persistent student bullying despite intervention efforts, with disciplinary measures like suspensions and punishments predominantly employed. Conversely, restorative interventions, anti-bullying programs, and supportive measures were underutilized, demonstrating ineffectiveness in bullying eradication. The study underscores the prevalence of student bullying in secondary schools, attributing it to the inadequate implementation of interventions. Recommendations urge school principals and stakeholders to enhance the efficacy of bullying interventions in secondary education settings.